The effects of tenapanor on serum fibroblast growth factor 23 in patients receiving hemodialysis with hyperphosphatemia. Issue 2 (3rd April 2018) - Block, Geoffrey A; Rosenbaum, David P; Yan, Andrew; Greasley, Peter J; Chertow, Glenn M; Wolf, Myles
Abstract: Background: Elevated serum fibroblast growth factor 23 (FGF23) is strongly associated with cardiovascular risk and mortality. Tenapanor, an inhibitor of gastrointestinal sodium/hydrogen exchanger isoform 3, decreased serum phosphate in a randomized, double-blind, placebo-controlled Phase 2 trial (ClinicalTrials.gov identifier NCT02081534) of patients receiving hemodialysis with hyperphosphatemia. Here, we report a secondary analysis of effects on serum FGF23 during that study. Methods: After 1–3 weeks of washout of phosphate binders, 162 patients were randomized to receive 4 weeks of treatment with placebo or one of six tenapanor regimens (3 or 30 mg once daily, or 1, 3, 10 or 30 mg twice daily). Intact FGF23 concentrations were determined from serum samples collected at screening, post-washout and end of treatment, assayed in duplicate in a single batch at the end of the study. Results: After phosphate-binder washout, serum FGF23 concentrations increased in all groups [range of geometric means: 1430–2605 pg/mL before, to 2601–6294 pg/mL after washout (P < 0.001 for all patients analyzed as a single group)]. Serum FGF23 concentrations subsequently decreased in tenapanor-treated patients (2030–3563 pg/mL), whereas they increased further in placebo-treated patients (6930 pg/mL). In an analysis of covariance, FGF23 decreased by 9.1–27.9% in tenapanor-treated patients and increased by 21.9% in placebo-treated patients (P ≤ 0.001–0.04). Conclusions: Following a marked increase in serum FGF23 in response to withdrawal of phosphate binders, tenapanor significantly decreased serum FGF23 in patients receiving hemodialysis with hyperphosphatemia. Further studies are required to explore the long-term effects of controlling FGF23 with tenapanor.